Antimicrobial activity and mode of action of 1,8-cineol against carbapenemase-producing Klebsiella pneumoniae - Moo, Chew Li; Osman, Mohd Azuraidi; Shun, Kai Yang; Wai, Sum Yap; Ismail, Saila; Swee, Hua Erin Lim; Chong, Chou Min; Lai, Kok Song (Nature Research, 2021)
Antimicrobial resistance remains one of the most challenging issues that threatens the health of people around the world. Plant-derived natural compounds have received considerable attention for their potential role to mitigate antibiotic resistance. This study was carried out to assess the antimicrobial activity and mode of action of a monoterpene, 1,8-cineol (CN) against carbapenemase-producing Klebsiella pneumoniae (KPC-KP). Results showed that resazurin microplate assay and time-kill analysis revealed bactericidal effects of CN at 28.83 mg/mL. Zeta potential showed that CN increased the surface charge of bacteria and an increase of outer membrane permeability was also detected. CN was able to cause leakage of proteins and nucleic acids in KPC-KP cells upon exposure to CN and ethidium bromide influx/efflux experiment showed the uptake of ethidium bromide into the cell; this was attributed to membrane damage. CN was also found to induce oxidative stress in CN-treated KPC-KP cells through generation of reactive oxygen species which initiated lipid peroxidation and thus damaging the bacterial cell membrane. Scanning and transmission electron microscopies further confirmed the disruption of bacterial cell membrane and loss of intracellular materials. In this study, we demonstrated that CN induced oxidative stress and membrane damage resulting in KPC-KP cell death.